An under-diagnosed geriatric syndrome: sleep disorders among older adults - TUFAN ÇİNÇİN, ASLI (MAKERERE UNIV, FAC MED, 2017)
Introduction: Sleep disorders are commonly under-diagnosed in the geriatric population. We aimed to determine the prevalence of sleep problems among older adults admitted to the geriatrics out-patient clinic. Methods: Two hundred and three patients (136 female) older than 75 years of age were included in the study. Patients underwent comprehensive geriatric assessment, including identification of sleep problems using the Sleep Disturbance Scale, Rapid eye movement (REM) sleep behavior disorder (RBD) Single-Question Screen questionnaire (RBD1Q) and The Johns Hopkins Restless Leg Syndrome Severity Scale. Demographic and clinical data including age, sex, medications, comorbid diseases, body mass index and functional scores was noted. Results: The mean age of the patients was 80.92 +/- 4.3 years. 35.5% of the patients had findings of REM-SBD and 32.5% of the patients had restless legs syndrome. Ninety-seven percent of the patients answered 'yes' to at least one of the sleep disturbance scale questions. There was no significant difference between male and female groups. Conclusion: We observed that sleep disorders were common among older adults. For this reason, the course and quality of sleep should be examined in all patients as a routine part of comprehensive geriatric assessment.
Keywords: Comprehensive geriatric assessment; older adults; sleep disorders; BEHAVIOR DISORDER; HIP-FRACTURES; INSOMNIA; COMPLAINTS; FALLS; RISK; PATHOPHYSIOLOGY; DISTURBANCES; PREVALENCE; DISEASE